RII type three term relations for bivariate polynomials orthogonal with respect to varying weights - Bracciali, Cleonice F. [UNESP]; Delgado, Antonia M.; Fernández, Lidia; Pérez, Teresa E. (Springer Nature, 2025)
Given a bivariate weight function defined on the positive quadrant of R2$$\mathbb {R}^2$$, we study polynomials in two variables orthogonal with respect to varying measures obtained by special modifications of this weight function. In particular, the varying weight functions are given by the multiplication of x1-nx2-n$$x_1^{-n}x_2^{-n}$$ times the original weight function. Apart from the question of the existence and construction of such kind of orthogonal polynomials, we show that the systems of bivariate polynomials orthogonal with respect to this kind of varying weights satisfy RII$$\hbox {R}_{{II}}$$ type three term relations, one for every variable. A method to construct bivariate orthogonal systems with respect to varying weights based in the Koornwinder’s method for generate standard bivariate orthogonal polynomials is developed. Finally, several examples and particular cases have been analysed.